Analisis Determinan Persepsi Masyarakat Mengenai Kesehatan Lingkungan di Sentra Industri Jumputan Tuan Kentang Kertapati Palembang - Meriyani, Depita; Zulkifli, Hilda; Faizal, Muhammad (Jurnal Kesehatan, 2019)
The existence of a jump cloth industry in the Palembang Kertapati Potatoes as many as 26 home industries as the central center of the fabric industry in Palembang City has had a positive impact as well as a negative impact. The positive impact of the availability of jobs for the surrounding community while the negative impact is causing water pollution. The purpose of the study was to analyze community perceptions, especially related to public health, near the jump center industrial location in Tuan Kentang Village, Jakabaring District, Palembang. The study population was 521 families. The sample of 105 households by stratified random sampling is a community that lives around the jump center industrial center. This study uses a quantitative method, with a cross-sectional design. The instrument of data collection in the form of a questionnaire based on the health belief model concept, interviews, and observations, the data were analyzed by multiple logistic regression. The results showed that community perceptions (53.3%) of public health-related industries were categorized as poor. Chi-Square test results showed a relationship between age (p-value 0.009), gender (p-value 0.003), education level (p-value 0.019) and environmental sanitation conditions (p-value 0.031) to community perceptions. It was concluded that age has a relationship with people's perception of the jumputan industry center in the city of Palembang.